2020
DOI: 10.1021/acs.jpca.0c01239
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the (Poly)Radicaloid Nature of Real-World Organic Compounds with DFT-Based Methods

Abstract: Recent advances in the synthesis of stable organic (open-shell) polyradicaloids have opened their application as active compounds for emerging technologies. These systems typically exhibit small energy differences between states with different spin multiplicities, which are intrinsically difficult to calculate by theoretical methods. We thus apply here some DFT-based variants (FT-DFT, SF-DFT, and SF-TDDFT) on a test set of large and real-world molecules, as test systems for which such energy differences are ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 111 publications
4
7
0
Order By: Relevance
“…The SC‐NEVPT2 correction significantly decreases the SA‐CASSCF results for S1S0 and T1S0 excitation energies of 2T‐4N and 2T‐7N, provinding in all cases very consistent results. Looking at the radicaloid nature of the ground‐state ( S 0 ) of these systems, as given by the integrated number of electrons ( N U ) housed on fractionally occupied orbitals, [68–70] see details as Supplementary Material, we can see a transition from moderately (mono)radicaloid (NU=0.75 for 2T‐N) to negligibly radicaloid (NU=0.26 character for 2T‐7N), passing through an intermediate value of NU=0.37 character for 2T‐4N.…”
Section: Resultsmentioning
confidence: 99%
“…The SC‐NEVPT2 correction significantly decreases the SA‐CASSCF results for S1S0 and T1S0 excitation energies of 2T‐4N and 2T‐7N, provinding in all cases very consistent results. Looking at the radicaloid nature of the ground‐state ( S 0 ) of these systems, as given by the integrated number of electrons ( N U ) housed on fractionally occupied orbitals, [68–70] see details as Supplementary Material, we can see a transition from moderately (mono)radicaloid (NU=0.75 for 2T‐N) to negligibly radicaloid (NU=0.26 character for 2T‐7N), passing through an intermediate value of NU=0.37 character for 2T‐4N.…”
Section: Resultsmentioning
confidence: 99%
“…Contrary to electron bipolarons, hole B+(S) presents a BS solution at the monomer level (BBL1) already, with Δ E = 0.5 and 1 eV for cis and trans , respectively. This is a remarkable aspect, because it highlights the multireference (MR) and polyradicaloid character [ 28 ] of the double charged (bipolaron) hole‐wavefunction.…”
Section: Resultsmentioning
confidence: 99%
“…In general, the presence of low energy BS‐UDFT solutions, regardless the nature of the charge, highlights a complex electronic structure scenario in which static electron correlation (SEC) and MR effects play relevant role. [ 29 ] Despite BS‐UDFT is based on a single‐determinant approach, [ 30 ] it has been demonstrated that it can qualitatively describe situations in which SEC [ 24b‐g,31 ] and MR or polyradical characters are predominant, [ 28,32 ] providing reasonable results in comparison to MR methods. [ 24b‐g,33 ] Unquestionably, high‐level quantum chemical methods, such as quantum Monte Carlo (QMC) techniques combined with the resonating‐valence‐bond (RVB) theory, [ 34 ] would provide a better description of the electronic structure and correlation effects as compared to BS‐UDFT or wavefunction MR techniques, however such approaches are still too demanding to be applied for polymeric materials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitatively speaking, we define the (poly)radicaloid character of any compound by the index (y 0 , y 1 ) arising from the fractional occupation (y i ) of the LUMO and LUMO+1 orbitals, respectively. [ 33 ] A pure closed‐shell, diradical, or tetraradical system will thus exhibit ideal (y 0 , y 1 ) values of (0,0), (1,0), and (1,1), respectively, with more moderate values meaning diradicaloid or tetraradicaloid character. In this case, we obtain (0.19,0.02), (0.35,0.04), and (0.52,0.08) values for AA‐Ar, TT‐Ar, and PP‐Ar, respectively, which indicates a progressive increase of their radicaloid character with system size.…”
Section: Resultsmentioning
confidence: 99%